PENCUCIAN BAHAN ORGANIK TANAH PADA TIGA PENGGUNAAN LAHAN DI DAERAH HUTAN HUJAN TROPIS SUPER BASAH PINANG-PINANG GUNUNG GADUT PADANG - Yulnafatmawita Yulnafatmawita; Adrinal Adrinal; Arief Fauzan Hakim (Jurnal Solum, 2011)
Study about soil organic matter (SOM) leaching in soil profiles of tropical rain forest was conducted in Bukit Pinang-Pinang, the upper footslope of Mt. Gadut in West Sumatra, and in Soil Physical laboratory Andalas University Padang.  Bukit Pinang-Pinang is located on 480-640 m asl and geographically is between 100°29’40” and 100°30’20 E”  as well as between 0°54’55” and 0°55’45”S.  This rain forest area is known as a super wet area because it receives high annual rainfall (>3500 mm).  The objective of this research was to measure the amount of SOM leached from top soil into the deeper soil.  Undisturbed soil samples were taken from three different land uses, forest, bush, and mixed garden, on the top, middle, and foot slopes.  Undisturbed soil samples were leached with distilled water as the amount of rainfall accepted in natural condition. The results showed that, land use change from forest into ecosystems of mixed garden (for over 50 years with 100% soil surface coverage and without any cultivation) and bush land (for over 20 years left) did not cause the SOM content in the profiles decreased. Amount of SOM leached from the top 0-10 cm was found greater from mixed garden, then followed by forest on the upper slope, forest on the middle slope, and bush area.Keywords: SOM leaching, land use change, tropical rain forest, bush, mixed garden